Multi-level labelling: Too complex for consumers? - Ramona Weinrich; Annabell Franz; Achim Spiller (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2015)
As more food labels enter the retail market, it is becoming increasingly difficult for consumers to review the underlying standards of products. The most common labels communicating ethical values tend to be binary. However, many attributes, such as animal welfare, are of a continuous nature and are not binary. One solution to communicate differentiated information about the process or product standards is through the use of multi-level labels, which indicate various levels of standards. This way, consumers might realize the differences in the production or process qualities more easily. However, since multi-level labels are more complex, the impact on consumers' comprehension is not clear. The objective of this paper is to test whether a multi-level labelling approach is comprehensible for consumers and could therefore be an effective tool to communicate information about standards and thus enhancing willingness to pay. The results show that when an explanation about the levels of the label is provided, there is an increasing willingness to pay for products with higher standards of animal welfare. Hence, a multi-level label can work if information is provided.
Keywords: 330; labelling; multi-level labelling; binary labels; animal welfare; consumer research